I dati INVALSI come strumento per migliorare la didattica della Matematica IV Seminario "I dati INVALSI: uno strumento per la ricerca e per la didattica" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
Mathematics is a fundamental part of human thought and the literature highlights its need for reflective citizens in order to better understand people, the society and the world. It actually encourages logical reasoning and mental rigor, playing a crucial role in understanding the contents of other school subjects. This book collects papers, submitted at IV edition of the Seminar "INVALSI data: a research and teaching tool" held in Rome from 29th November to 1st December 2019, by both teachers and researchers about the didactics of mathematics, to debate and deepen this topic, sharing ideas, suggestions, and experiences. INVALSI data could be a useful tool to find new paths to help schools to improve teaching and learning process, indeed.